The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0102-86502012001200011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of S-methylisothiourea hemisulfate, an inducible nitric oxide synthase inhibitor, on the healing of colonic anastomosis in rats

Abstract: PURPOSE:To evaluate the effects of S-methylisothiourea hemisulfate (SMT) on the healing of colonic anastomosis in rats. METHODS:Sixty rats Wistar were distributed into two groups of 30 animals: experimental (E) and control C). The animals of experimental group received intraperitoneal SMT at 50mg/kg/dose every 12 hours for 72 hours. The control group received intraperitoneal saline at the same volume of SMT. The rats were subdivided into subgroups groups of 10 for euthanasia on the third, seventh, and 14 th po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…SMT is an iNOS inhibitor, and some studies have shown the specificity of SMT for iNOS. [ 12 15 ] Nitrite is also considered as an indicator of NO production. [ 16 ] We found that simultaneous use of SMT and iron did not attenuate the intensity of ID in the kidney.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SMT is an iNOS inhibitor, and some studies have shown the specificity of SMT for iNOS. [ 12 15 ] Nitrite is also considered as an indicator of NO production. [ 16 ] We found that simultaneous use of SMT and iron did not attenuate the intensity of ID in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…The agent is shown to be 10–30 times more effective and powerful than other iNOS inhibitors in vitro . [ 12 ] SMT inhibits NO production, which in turn reduces endogenous NO concentration. [ 13 ] Due to increase of iNOS in some organs [ 10 11 ] by iron overloading, it is hypothesized that inhibition of iNOS may attenuate iron overloading or at least it's side effects.…”
Section: Introductionmentioning
confidence: 99%